A novel latency-active promoter is contained within the herpes simplex virus type 1 UL flanking repeats. - Goins, W F (1994)
Herpes simplex virus type 1 (HSV-1) expresses a unique series of RNA molecules, the latency-associated transcripts or LATs, during latent infection of neuronal tissues. Previous studies by others have described a TATA box-containing latency-active promoter, referred to here as LAP1, located approximately 700 bp upstream of the 5' end of the major 2.0-kb LAT. In this report, transient gene expression assays were employed to identify a second, novel latency-active promoter (LAP2) present within a region downstream of LAP1 and 5' proximal to the major 2.0-kb LAT. In contrast to LAP1, this promoter lacks a TATA box but possesses cis-acting regulatory elements and other features frequently observed within eukaryotic housekeeping gene promoters. Unlike most other HSV promoters, LAP2 was down-regulated by the viral transcriptional activators ICP4 and ICP0. The majority of LAP2-positive regulatory elements were located within sequences from -257 to -58 relative to the 5' end of the 2.0-kb LAT, and the basal promoter mapped within sequences from -14 to +28. RNase protection experiments demonstrated that chimeric LAT-chloramphenicol acetyltransferase transcripts produced in the transient assays initiated at or near the 5' end of the major 2-kb LAT. Tn5 insertional mutagenesis of the ICP4 regulatory gene determined that down-regulation of LAP2 required the ICP4 transactivating domain and targeted the minimal promoter region as the site of action by ICP4. Replicating recombinant viruses containing a LAP2-lacZ reporter gene cassette in an ectopic site (glycoprotein C locus) were shown to be active in mouse trigeminal ganglia. Taken together, these experiments suggest that the LAT region of the HSV-1 genome contains at least two latency-active promoters which may play different roles in expressing the various LATs. Alternatively, these promoters may comprise a larger promoter-regulatory complex which may influence transcription during latency.